The complete chloroplast genome sequence of Melastoma candidum (Melastomataceae) - Wei Lun Ng; Yacheng Cai; Wei Wu; Renchao Zhou (Mitochondrial DNA. Part B. Resources, 2017)
The plant genus Melastoma is comprised of members estimated to have formed through recent species radiation. Natural hybridization among member species further complicates taxonomy within the genus. Herein, we report the complete chloroplast genome of M. candidum, assembled from partial data obtained from a parallel whole-genome Illumina paired-end sequencing effort on the species. The chloroplast genome was 156,682 bp in length, with a large single-copy (LSC) region of 86,084 bp, a small single-copy (SSC) region of 17,094 bp, separated by two inverted repeat (IR) regions of 26,752 bp each. It was predicted to contain a total of 129 genes, with an overall GC content of 37.17%. Phylogenetic analysis placed M. candidum in the same clade as species within the Melastomeae tribe of Melastomataceae.